2021
DOI: 10.12659/ajcr.931263
|View full text |Cite
|
Sign up to set email alerts
|

Hydralazine-Induced Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: Asymptomatic and Renal-Restricted Presentation

Abstract: Patient: Female, 66-year-old Final Diagnosis: Hydralazine induced ANCA-associated vasculitis Symptoms: Asymptomatic Medication:— Clinical Procedure: — Specialty: Nephrology • Rheumatology Objective: Rare disease Background: Hydralazine, a potent vasodilator widely used to treat hypertension, has been implicated in an increasing number of cases of drug-induced autoimmune diseases in recent years. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Other drug-induced causes of AAV include montelukast, minocycline, rituximab, tumor necrosis factor-ɑ inhibitors (etanercept, infliximab, adalimumab, golimumab), and anti-thyroid drugs (methimazole, propylthiouracil, carbimazole, and benzyl thiouracil). Risk factors for drug-induced renal injury include old age (>60 years), female gender, diabetes, heart failure, and pre-existing renal insufficiency [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other drug-induced causes of AAV include montelukast, minocycline, rituximab, tumor necrosis factor-ɑ inhibitors (etanercept, infliximab, adalimumab, golimumab), and anti-thyroid drugs (methimazole, propylthiouracil, carbimazole, and benzyl thiouracil). Risk factors for drug-induced renal injury include old age (>60 years), female gender, diabetes, heart failure, and pre-existing renal insufficiency [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the absence of other symptoms, positive AHA is not diagnostic of DIL [ 10 , 11 ]. Patients with HIG have severe progression compared to those with DIL because of vasculitis of vessels of kidneys, and therefore require aggressive immunosuppressant treatment [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, only 4 studies have described kidney-limited presentation of hydralazine-induced ANCA-associated vasculitis. [3][4][5][6][7] We review this case to discuss and highlight the importance of a high degree of clinical acumen, and early diagnosis for better clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Hydralazine induced vasculitis was rst described in the 1980s [2]. Since then, multiple case studies have reported this phenomenon [3][4][5]. The case studies have reported three frequent clinical manifestations: glomerulonephritis, cutaneous small vessel vasculitis and bilateral interstitial in ltrates.…”
Section: Introductionmentioning
confidence: 99%